Failure Mechanism Identification of Hook Components in Automatic Machines Using Visual and Material Analysis - RAHMAWATI, NABILA DESY; LUTIYATMI (Talenta Publisher, 2025)
The hook component in automatic packaging machines frequently experiences premature failure, leading to increased downtime, higher maintenance costs, and reduced production efficiency. This study aims to identify the failure mechanism of the hook through visual inspection, maintenance data analysis, and material characterization. Visual examination was conducted on broken hook specimens to identify fracture morphology and surface characteristics. Historical maintenance records from 2017 to 2024 were analyzed to identify the frequency and type of failure. Chemical composition testing was performed using Optical Emission Spectroscopy (OES), while Rockwell hardness testing (HRC) evaluated the material’s mechanical properties. The results revealed that the failure mode was categorized as brittle fracture, indicated by flat and granular fracture surfaces without plastic deformation. The main failure factor was the direct impact between the hook and the punch, caused by misalignment due to bearing wear. The material, classified as medium carbon steel with 0.599 wt.% C and 1.000 wt.% Mn, exhibited high hardness but low toughness, leading to a brittle fracture under impact loading. Surface hardening combined with light tempering and shot peening is recommended to improve wear resistance and toughness, thereby reducing the risk of brittle fracture.